Constructing protocells: a second origin of life - Rasmussen, Steen; Albertsen, Pedersen y Svanerborg, Albertsen, Pedersen y Svanerborg (Pensamiento. Revista de Investigación e Información Filosófica, 2013)
What is life? How does non living materials become alive? How did the first living cellsemerge on Earth? How can artificial living processes be useful for technology? These are the kinds ofquestions we seek to address by assembling minimal living systems from scratch.